Disintermediation and Monetary Transmission in Canada - Roldos, Jorge (IMF Working Papers; Working Paper ;, 2006)
This paper studies changes in Canada's monetary policy transmission, associated with the important changes in financial structure experienced in the 1990's, using two methodologies. First, VAR models show a clear break in monetary transmission beginning in 1988, after changes in financial regulation initiated the process of financial disintermediation. Second, estimates of the interest rate elasticity of aggregate demand in IS equations increase in the 1990's, suggesting that the systematic component of monetary policy has become more relevant. The ratio of direct to indirect finance, a measure of disintermediation, contributes to explain changes in the interest rate elasticity, suggesting an increased effectiveness of monetary policy associated with a larger use of market-based sources of finance.